Mushroom Poisoning-an overview - Patowary, BS (Journal of College of Medical Sciences-Nepal, 2010)
There are many thousands of mushroom species in the world, some are edible and some are poisonous due to containing significant toxins. The edible mushroom is a common food item with tempting flavour, taste and nutritive value; nowadays quite often grown at home and cultured with commercial marketing. Mushroom poisoning usually results from ingestion of wild mushrooms due to misidentification of a toxic mushroom as an edible species bearing very close resemblance, deliberate seeking of psychotropic mushrooms and accidental childhood ingestions. Majority of fatal mushroom poisoning occurs due to ingestion of Amanita Phalloides - the 'death cap', due to its high content of Amatoxin - a potent cytotoxin. Fatal poisoning is usually associated with delayed onset of symptoms which are very severe, with hepatic, renal, hemolytic and CNS involvement. Aim of this article is for informational and preventive purpose. Key words: Mushroom poisoning; amanita phalloidis; amatoxin. DOI: 10.3126/jcmsn.v6i2.3619 Journal of college of Medical Sciences-Nepal, 2010, Vol.6, No-2, 56-61